North American Monsters: A Contemporary Legend Casebook, edited by David J. Puglia - Bullard, Eddie (Journal of Scientific Exploration, 2023)
Who doesn’t love a good monster story? A delicious chill shimmies up the spine and tingles the hairs of listeners huddled around a dying fire on an autumn night as clouds cross the moon and extinguish its light, while the narrator’s hushed voice winds the taut wire of terror to the breaking point. And then dry leaves crackle somewhere off in the dark. Anyone indifferent to the monster lurking just beyond the firelight is surely a dead soul…though I hesitate even to think the thought, lest a new monster be born. This world and every world visited by the human imagination comes well-stocked with monsters. They have always been with us and remain robust in modern times. The realm of folklore with its giants, witches, trolls, and dragons gave many of us our first unnatural scares, and no scholarly discipline than folklore seems more tailor-made to study their cause. North American Monsters undertakes that responsibility with an anthology of nineteen articles, fourteen drawn from scholarly journals and five written for this volume, each committed to the understanding of monsters in contemporary legends. Ah, the scholarly anthology. It often suggests a dutiful assemblage of dust-dry writing where the reader soon sleeps a sleep akin to coma and where all hopes of joy and excitement go to die. Well, this one is quite something more. Far from dull and dreary, here is a collection worthy of its subject. Editor David Puglia has chosen lively articles based on the authors’ field research to introduce a range of fearsome creatures, some long-lived, some deceased, some recent and still walking among us. Beyond passing acquaintance, these articles familiarize the reader with their subjects, how these monsters are born and grow and die, the environments that favor them, the human energies that feed and sustain them. We get to know them. Sometimes they are villains, forces of nature, even tragic figures, but all of them have a purpose in the human realm that goes beyond eating people or leaving tracks and turds in the forest.